(untitled) (Bangladesh Journal of Medical Science, 2021)
After the last flu pandemic in 1918, the world has not faced a similar pandemic until now. However, it has been possible to identify the causative agent as well as its structure and function. The SARS-CoV-2 virus attacks the respiratory system, and the viral components like the spike protein and nucleocapsid protein produce an immune response in the host for viral elimination. The antigen can be recognized by or is presented to T cells. This results in neutralizing antibody production, cytokine secretion, and cytolysis. Although most infected individuals only suffer mild or moderate disease, some develop cytokine storms due to excess formation of cytokines resulting in ARDS, multiorgan failure, and DIC. The virus has mechanisms in place that can aid its escape from the host’s immune response. Vaccine development has been underway around the globe to produce effective vaccines to limit morbidity and mortality from infection. Vaccines like mRNA vaccines encode the spike protein of coronavirus, and research has shown that antibodies developing from the vaccine were less affected by mutation in the spike protein of the virus than that developed from infection. The mRNA vaccine has modified nucleotide that limits the excessive formation of Interferons. Although various hurdles to overcome to vaccinate the world population effectively, vaccination may be essential to control the pandemic and a return to normalcy. This review highlights the current knowledge on the structure of the virus and the immune response triggered by the virus in infected individuals. It also reviews the currently available vaccines with their formulation, mechanism of immune response elicited. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.32-40